A novel soft matter composite material for energy-saving smart windows: from preparation to device application1. Issue 20 (28th May 2015) - Gao, Yanzi; Yao, Wenhuan; Sun, Jian; Zhang, Huimin; Wang, Zhendong; Wang, Ling; Yang, Dengke; Zhang, Lanying; Yang, Huai
<x xml:space="preserve">Abstract</x> A novel soft-matter composite film of ethylene-vinyl acetate and liquid crystal with an energy conservation efficiency of 40.4% is developed.